Implementasi Prinsip Rahmatan Lil ‘Alamin Dalam Pendidikan Ekologi: Strategi Mewujudkan Harmoni Manusia Dan Alam - Sri Wahyuni; Darmawati (CV. Multi Kreasi Media, 2025)
This study aims to analyze the implementation of the Rahmatan lil 'Alamin principle in ecological education as a strategy to realize harmony between humans and nature in the Pamulang Campus environment. The Rahmatan lil 'Alamin principle, which emphasizes the values ​​of compassion, justice, and responsibility towards all creation, is used as a normative basis in developing ecological awareness of the academic community. This study uses a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with lecturers, students, and campus administrators, and analysis of institutional documents related to campus environmental policies and practices. Data analysis techniques were carried out through data reduction, data presentation, and thematic conclusion drawing. The results of the study indicate that the implementation of the Rahmatan lil 'Alamin principle in ecological education at the Pamulang Campus is realized through the integration of Islamic values ​​in the curriculum, the habituation of environmentally friendly behavior, and green campus programs such as waste management, reforestation, and efficient use of resources. However, challenges are still found in the aspects of consistency of implementation and active participation of the entire academic community. This study concludes that Rahmatan Lil 'Alamin-based ecological education has the potential to be a strategic approach to building harmony between humans and nature on campus, as long as it is supported by sustainable institutional policies and a participatory academic culture.